A highly effective and stable CuZn0.3MgxAlOy catalyst for the manufacture of chiral l-phenylalaninol: the role of Mg and its hydrotalcite-like precursor. Issue 10 (24th December 2015) - Shi, Zhangping; Zhang, Shuangshuang; Xiao, Xiuzhen; Mao, Dongsen; Lu, Guanzhong
Abstract : A highly effective and stable CuZn0.3 Mg0.1 AlO y catalyst derived from a Cu-rich hydrotalcite-like precursor was prepared for the catalytic hydrogenation ofl -phenylalanine methyl ester tol -phenylalaninol with 100% ee selectivity. Abstract : Highly effective CuZn0.3 Mg x AlO y ( x = 0–0.2) catalysts for the synthesis of chirall -phenylalaninol derived from Cu-rich hydrotalcite-like precursors were prepared by a co-precipitation method with Na2 CO3 as the precipitant, and their physicochemical and catalytic properties were characterized. The results show that the presence of Mg 2+ ions can promote the formation of hydrotalcite-like (htl) precursors, and the Mg 2+ content would affect the phase purity of the prepared htl precursors. The BET surface area, exposed copper surface area and amount of acid sites of the samples decreased with the increase in the molar ratio of Mg 2+ /Al 3+ . Also, the dense layered htl precursors are beneficial to the atomically uniform distribution of the corresponding metal oxides in the prepared catalysts, promoting the stronger interaction between Cu 0 and Al2 O3 after the catalysts were reduced (SMSI effect). The activity of the CuZn0.3 Mg x AlO y catalysts is greatly dependent on not only the metallic copper surface area, but also the SMSI effect and the acidity of the catalysts. When Mg 2+ /Al 3+ = 0.1 (mol), a phase-pure htl precursor could be obtained, and after calcination, the prepared CZA-0.1 catalyst exhibited very excellent catalytic performance for the hydrogenation ofl -phenylalanine methyl ester to chirall -phenylalaninol. After 5 h of reaction at 110 °C and 4 MPa H2, 100% conversion ofl -phenylalanine methyl ester and 91.1% yield ofl -phenylalaninol with an ee value of 100% were achieved. After recycling 13 times, thel -phenylalaninol selectivity of the CZA-0.1 catalyst only decreased by 7.2%.